2019
DOI: 10.1159/000504609
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transcranial Alternating Current Stimulation for the Treatment of Chronic Insomnia: A Randomized, Double-Blind, Parallel-Group, Placebo-Controlled Clinical Trial

Abstract: <b><i>Background:</i></b> Not all adults with chronic insomnia respond to the recommended therapeutic options of cognitive behavioral therapy and approved hypnotic drugs. Transcranial alternating current stimulation (tACS) may offer a novel potential treatment modality for insomnia. <b><i>Objectives:</i></b> This study aimed to examine the efficacy and safety of tACS for treating adult patients with chronic insomnia. <b><i>Methods:</i></b>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 35 publications
2
49
0
Order By: Relevance
“…The government and psychologists should constantly focus on the mental health of the public during this unique period. Furthermore, our study found that anxiety was associated with economic loss, a history of physical disease, and increased ISI scores, which is in line with previous studies ( 8 , 29 , 30 ). Interestingly, our study also demonstrated that anxious people were likely to have more somatic symptoms than people without anxiety symptoms.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The government and psychologists should constantly focus on the mental health of the public during this unique period. Furthermore, our study found that anxiety was associated with economic loss, a history of physical disease, and increased ISI scores, which is in line with previous studies ( 8 , 29 , 30 ). Interestingly, our study also demonstrated that anxious people were likely to have more somatic symptoms than people without anxiety symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…The government and psychologists should constantly focus on the mental health of the public during this unique period. Furthermore, our study found that anxiety was associated with economic loss, a history of physical disease, and increased ISI scores, which is in line with previous studies (8,29,30).…”
Section: Discussionsupporting
confidence: 93%
“…Our report found potential risk factors for medical health workers to develop insomnia, anxiety, depression, obsessive-compulsive symptoms, and somatization. Undoubtedly, these risk factors might endure allostatic overload and favor the development of psychopathology, including chronic insomnia [29]. Independent factors (i.e., currently having organic disease, living in rural areas, being at risk of contact with COVID-19 patients in hospitals, or being female) were common risk factors for insomnia, anxiety, depression, and obsessive-compulsive symptoms among medical health workers.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of employees experiencing burnout is dramatically increasing in Europe (Eurofound, 2018), which has a significant socio-economic impact. Burnout consists of three components: (1) exhaustion at the physical level (energy loss, fatigue, weakness, physical and psychosomatic complaints), the mental level (negative behavior towards oneself, work, or life in general), or the emotional level (feelings of being trapped in a situation, helplessness, or hopelessness); (2) depersonalization or alienation towards the actual work, towards patients or pupils, etc. (Demerouti et al, 2001;Schaufeli & Enzmann, 1998); (3) and reduced professional performance, which can be attributed to depersonalization and alienation (Demerouti et al,2001).…”
Section: Introductionmentioning
confidence: 99%